Joint pain and swelling prevalence in residents of different regions of Russian Federation (preliminary results) - Sh F Erdes; E A Galushko; L A Bahtina; T. Y. Bolshakova; I. B. Vinogradova; N. V. Zabrodchenko; O N Ivanova; N N Kroliina; O M Lesnyak; L V Menshikova; N M Naumova; T N Petrachkova; et al. (Научно-практическая ревматология, 2004)
Objective. To reveal in a population sample people with joint pain and swelling. Material and methods. A screening questionnaire for revelation arthritis and arthralgia was filled for each adult resident of 18 years or older. Screening examination was performed in country and city samples. Universal examination was performed among country residents, representative sample was formed for city residents. Results. 23438 residents were screened, mean age was 48,1 ±17,6 years. Women were prevalent - 60%. 8016 were city and 15422 - country residents. Joint pain prevalence was 45%, joint swelling - 27%. These symptoms disappeared with time in 7% and 6% respectively. In other people they became chronic. Population prevalence of joint complaints is connected with sex and depends on age. In people younger than 20 years of age prevalence of joint pain was 9% and swelling - 3%. Conclusion. Preliminary analysis of the screening part of the study showed scale of the joint pathology problem and allowed to get the first data on prevalence of arthralgia and arthritis in Russia.